Rice bran oil based biodiesel production using calcium oxide catalyst derived from Chicoreus brunneus shell. (1st February 2018) - Mazaheri, Hoora; Ong, Hwai Chyuan; Masjuki, H.H.; Amini, Zeynab; Harrison, Mark D.; Wang, Chin-Tsan; Kusumo, Fitranto; Alwi, Azham
Abstract: Environmental pollution and the declining global supply of accessible fossil fuels are the key drivers of the search for alternative sources of energy. Biodiesel, a renewable liquid transport fuel, is commercially-produced using heterogeneous catalysts. Heterogeneous catalysts obtained from seashells appeared as promising alternatives thanks to their low preparation cost and increased efficiency in transesterification. In this study, shells from Chicoreus brunneus (known as Adusta murex ) were calcined, hydrated, and dehydrated to produce CaO heterogeneous nanocatalyst for the transesterification of rice bran oil into biodiesel. Field emission scanning electron microscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, surface area measurement (Brunauer-Emmett-Teller method), and X-ray diffraction were used to characterise the seashell-derived catalyst. The properties of the rice bran oil-derived biodiesel (acid value, calorific value, density, oxidation stability, and flash point) conformed to the American Society of Testing and Materials (ASTM) D6751 and European EN 14214 biodiesel standards, except for kinematic viscosity. Therefore, the impact of the parameters used for production of the CaO heterogeneous nanocatalyst (calcination temperature and time) and the transesterification reaction (catalyst loading and methanol to rice bran oil ratio) on the kinematic viscosity of RBO-derived biodiesel were determined. A model for the transesterification process was developed using a combination of artificial neural networking with ant colony optimisation. The model predicted that C. brunneus -derived CaO catalyst prepared at 1100 °C for 72 min could be used to produce biodiesel from rice bran oil with a minimum kinematic viscosity (4.42 mm 2  s −1 ) confirming to both the ASTM D6751 and EN 14214 biodiesel standards in a transesterification reaction operating with a 35:1 methanol to rice bran oil molar ratio and 0.5 wt% catalyst mass. Highlights: Chicoreus brunneus seashells-derived CaO catalyst was synthesized. Structure and properties of the catalyst were studied. The reusability of the catalyst was demonstrated for seven cycles. Kinematic viscosity was optimized using ant colony optimization method. Excellent catalytic activity with FAME yield of 93.5% was achieved.